Characterization of Lactococcus garvieae Isolated from Wadi Papuyu (Anabas testudineus Bloch) Fermentation of Indonesian Origin as a Probiotic Candidate - Soemarie, Yulistia Budianti; Pratama, Rizki Rahmadi; Milanda, Tiana; Barliana, Melisa Intan (Sciences of Pharmacy, 2025)
Lactococcus garvieae was isolated from the traditional fermented food Wadi Papuyu (Anabas testudineus Bloch) and characterized for its potential as a probiotic candidate. Growth assays demonstrated that L. garvieae could proliferate in MRS medium, reaching cell counts exceeding 107 CFU/mL after 72 h of anaerobic incubation. The isolate exhibited optimal growth at both 30 °C and 37 °C, as indicated by significant increases in absorbance at these temperatures. However, in the bile salt tolerance test using 0.5% (w/v) bile salts, L. garvieae showed a marked decline in growth, with absorbance values decreasing substantially after 24 and 48 h, indicating insufficient bile tolerance. The autoaggregation assay revealed values below 10%, suggesting limited autoaggregation capability and reduced potential for colonization in the gastrointestinal tract. In contrast, the co-aggregation assay showed that L. garvieae was able to coaggregate with pathogenic bacteria such as Escherichia coli, Salmonella spp., and Shigella spp., with co-aggregation percentages exceeding 40% after 5 h. Antimicrobial activity tests demonstrated that L. garvieae produced strong inhibition zones (diameters >10–20 mm and >20 mm) against Gram-positive and Gram-negative pathogenic bacteria. These findings indicate that while L. garvieae exhibits promising antimicrobial activity and co-aggregation ability, its limited bile salt tolerance and autoaggregation capacity are significant constraints in its development as a probiotic candidate.